A glimpse from the ancient world: What a gold necklace from Tillya-tepe reveals about opium in Afghanistan. Issue 2 (October 2020) - Peterson, Sara
Abstract : Among the six excavated burials at Tillya-tepe, in northern Afghanistan, was one occupied by an elite woman wearing a substantial necklace consisting of large gold beads shaped as seed-heads. The scale and fine workmanship of this necklace suggest that it was one of her most important possessions. It can be demonstrated that these large seed-heads are representations of poppy capsules, whose significance lies in the fact that they are the source of the potent drug opium. This necklace is the most outstanding object within a group of items decorated with poppy imagery, all of which were discovered in female burials. The opium poppy has long been a culturally important plant, and the implication of this identification is investigated in several contexts. Firstly, the proliferation of poppy imagery in the female burials at Tillya-tepe is examined, and then there is a discussion of material evidence for opium among relevant peoples along the Eurasian steppes. The particular cultural importance of opium is reviewed, leading finally to a proposal for the societal role of these women.